Ultra‐Steep‐Slope High‐Gain MoS2 Transistors with Atomic Threshold‐Switching Gate. Issue 8 (17th January 2022) - Lin, Jun; Chen, Xiaozhang; Duan, Xinpei; Yu, Zhiming; Niu, Wencheng; Zhang, Mingliang; Liu, Chang; Li, Guoli; Liu, Yuan; Liu, Xingqiang; Zhou, Peng; Liao, Lei
Abstract: The fundamental Boltzmann limitation dictates the ultimate limit of subthreshold swing (SS) to be 60 mV dec −1, which prevents the continued scaling of supply voltage. With atomically thin body, 2D semiconductors provide new possibilities for advanced low‐power electronics. Herein, ultra‐steep‐slope MoS2 resistive‐gate field‐effect transistors (RG‐FETs) by integrating atomic‐scale‐resistive filamentary with conventional MoS2 transistors, demonstrating an ultra‐low SS below 1 mV dec −1 at room temperature are reported. The abrupt resistance transition of the nanoscale‐resistive filamentary ensures dramatic change in gate potential, and switches the device on and off, leading to ultra‐steep SS. Simultaneously, RG‐FETs demonstrate a high on/off ratio of 2.76 × 10 7 with superior reproducibility and reliability. With the ultra‐steep SS, the RG‐FETs can be readily employed to construct logic inverter with an ultra‐high gain ≈2000, indicating exciting potential for future low‐power electronics and monolithic integration. Abstract : Ultra‐steep‐slope MoS2 resistive‐gate field‐effect transistors (RG‐FETs) by integrating atomic‐scale resistive filamentary with conventional MoS2 transistors, demonstrating an ultra‐low SS below 1 mV dec −1 at room temperature are reported. Ultra‐high gain ≈2000 is demonstrated in the fabricated inverter.